Teori Manajemen Konflik Dalam Pendidikan Islam - Nurul Hafshotus Shofirah; Amiroh Hilmi Wasalma; Isti Annisa; M. Roikul Ubbad; Mu’alimin Mu’alimin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Management is organizing that involves many people and working together to achieve goals. Within organizations, of course, there are differences of opinion, incompatibilities and contradictions which give rise to many conflicts, from small to large conflicts, both hidden and overt. There are positive, negative and neutral conflicts. There are four structures that often give rise to conflict, namely hierarchical conflict, functional conflict, line-staff conflict and formal-informal conflict. Conflict in an organization originates from three things, namely: communication problems, organizational structure and human factors. Furthermore, there are three stages that must be passed in an effort to resolve conflict, namely: conflict analysis planning, conflict evaluation and conflict resolution. Strategies for dealing with conflict can be through forcing, avoding, compromising, collaborating, and smoothing. The figures of classical sociological conflict theory are as follows Polybus, Ibn Khaldun, Nicolo Machiavelli, Jean Bodin, Thomas Hobbes. The modern sociological figures who put forward conflict theory are Karl Marx, Lewis A. Coser, Ralf Dahrendorf.